In vitro inhibitory effects of Sardinian Pistacia lentiscus L. and Pistacia terebinthus L. on metabolic enzymes: Pancreatic lipase, α‐amylase, and α‐glucosidase. Issue 1 (5th September 2014) - Foddai, Marzia; Kasabri, Violet; Afifi, Fatma U.; Azara, Emanuela; Petretto, Giacomo L.; Pintore, Giorgio; Tester, Richard F.
<x xml:space="preserve">Abstract</x> Pancreatic triacylglycerol lipase (PL), α‐amylase, and α‐glucosidase are appealing pharmacological targets for the management of dyslipidemia, atherosclerosis, and obesity‐diabetes. Presently, in vitro screening for considerable inhibition of these digestive hydrolases by endemic Sardinian Pistacia lentiscus L. and P. terebinthus L. leaves and fruits aqueous extracts (AEs) (Anacardiaceae) was undertaken. The AEs PL‐IC50 (µg/mL) in an ascending order were: P. lentiscus leaves; 6.1 ± 0.2<P. terebinthus leaves; 9.0 ± 0.4<P. terebinthus fruits; 125.2 ± 12.1<P. lentiscus fruits; 230.7 ± 38.4. Comparable to acarbose, all different parts of Sardinian Pistacia spp. AEs were identified as in vitro potent and efficacious dual inhibitors of α‐amylase and α‐glucosidase with respective IC50: P. lentiscus leaves; 65.3 ± 7.4 µg/mL<P. terebinthus leaves; 76.5 ± 4.5 µg/mL<P. terebinthus fruits; 237.7 ± 33.5 µg/mL<P. lentiscus fruits; 1.4 ± 0.2 mg/mL. Taken together, Sardinian Pistacia spp. as functional foods and nutraceuticals modulating gastrointestinal carbohydrate and lipid digestion and absorption, maybe be advocated as potential candidate for obesity‐diabetes prevention and phytotherapy.